2014
DOI: 10.1021/jf5017708
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Ameliorates Lens Protein Turbidity Formations by Inhibiting Calpain Proteolysis and Ultraviolet C-Induced Degradation

Abstract: Carnosine (CAR) is an endogenous peptide and present in lens, but there is little evidence for its effectiveness in calpain-induced proteolysis inhibition and its differential effects toward different wavelengths of ultraviolet (UV) irradiation. This study aimed to develop three in vitro cataract models to compare the mechanisms underlying the protective activities of CAR. Crude crystallins extracted from porcine lenses were used for antiproteolysis assays, and purified γ-crystallins were used for anti-UV assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The protective effects of Cur or other tested compounds were assayed via an in vitro anticataract screening system in which lens protein turbidity was induced by either sodium selenite or calcium ions. Porcine lenses were decapsulated and homogenized in lens buffer as described in our previously study. , After centrifuging at 16060 g for 30 min, the supernatant was collected, and the protein concentration was determined using the Bradford method (Bio-Rad Laboratories, USA). Lens proteins with buffer only were used as a control.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The protective effects of Cur or other tested compounds were assayed via an in vitro anticataract screening system in which lens protein turbidity was induced by either sodium selenite or calcium ions. Porcine lenses were decapsulated and homogenized in lens buffer as described in our previously study. , After centrifuging at 16060 g for 30 min, the supernatant was collected, and the protein concentration was determined using the Bradford method (Bio-Rad Laboratories, USA). Lens proteins with buffer only were used as a control.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Posterior capsule opacification (PCO), which is also known as secondary cataract, was characterized by cellular migration onto the posterior lens capsule, coupling with deposition of abnormal extracellular matrix and capsular wrinkling, all of which could lead to opacification of lens and ultimately cataract [35]. In addition, proteolysis is another typical characteristic in cataract formation [36][37][38]. Wang et al proposed that elevated proteolysis resulted from S129R mutation might induce pathology since significant decline of functional proteins changed the protein-protein interaction network [39].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, carnosine supplementation also downregulated the ubiquitinated proteins in HH‐exposed rats. Liao et al, 65 recently reported that carnosine protected lens proteins by inhibiting calpain proteolysis and UV‐C‐induced degradation.…”
Section: Discussionmentioning
confidence: 99%